Fabricação de Concreto com agregado de Argila Calcinada produzida com solo do Pólo Oleiro do Amazonas. - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The Amazonia area for geological formation doesn't have rocks of easy extraction for use in the building site, due to this, the natural gravel obtained of the dredging of the bed of the rivers, it is the great aggregate commercially more used for the concrete production. Due to that, the search of alternative aggregate has been a constant source of research. Therefore, this work presents a study of the characteristics and technological properties of two ceramic pastes, coming from the country of Iranduba and Manacapuru - AM, with the purpose of manufacturing synthetic aggregate of calcined clay for use in concrete. The ceramic pastes were submitted to analysis of X-ray diffraction ,chemical composition, particle size distribution and plasticity. Samples were made by uniaxial pressure at 20 MPa to burn in the following temperatures : 850, 950, 1050, 1150 oC. The technological properties evaluated were: linear shrinkage, water absorption, apparent specific mass and vitrification temperature. The ceramic paste that presented the smallest apparent specific mass and smallest percentile of molding humidity was chosed for synthetic aggregate. The results obtained for the concrete produced with the synthetic aggregate of calcined clay show its potential as a substitute of the natural aggregate of Amazonic region, the natural gravel, which, it demonstrated that with that application type it can be obtained a product with mechanical resistance satisfactory and smaller apparent specific mass, assisting like this the purpose of that research.
Keywords: Engenharia; Oleiro; ENGENHARIAS: ENGENHARIA CIVIL